Penerapan Discovery Learning untuk Meningkatkan Hasil Belajar IPAS Bagian Tumbuhan dan fungsinya pada PDBK Tunagrahita Fase B di SLBN Sukoharjo - Monalisa Wulandari; Sugini Sugini; Winarni Winarni (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2025)
This study aims to improve the learning outcomes of students in the subject of Natural and Social Sciences (IPAS) on the material “Plant Parts and Their Functions” through the application of the Discovery Learning approach. The subjects in this study were five Special Needs Learners (PDBK) with tunagrahita in SLB Negeri Sukoharjo. The method used is Classroom Action Research (PTK) which was carried out in two cycles in May 2025. Each cycle consists of planning, implementation, observation, and reflection stages. Data collection instruments use written tests in the form of LKPD to measure student learning outcomes. The achievement level criteria (KKTP) was set at 70. The results showed a significant increase from cycle I to cycle II. In cycle I, only three out of five learners managed to achieve the minimum KKTP score. After improvements and adjustments to the learning strategy in cycle II, four out of five learners managed to achieve scores above KKTP, with the overall average score increasing to 80. Based on the results it can be concluded that the application of the Discovery Learning approach is effective in improving learning outcomes and active involvement of PDBK tunagrahita in learning IPAS at SLB Negeri Sukoharjo.